Plasmid Transfer between the Bacillus thuringiensis Subspecies kurstaki and tenebrionis in Laboratory Culture and Soil and in Lepidopteran and Coleopteran Larvae - Thomas, D. John I. (American Society for Microbiology, 2000)
Plasmid transfer between Bacillus thuringiensis subsp. kurstaki HD1 and B. thuringiensis subsp. tenebrionis donor strains and a streptomycin-resistant B. thuringiensis subsp. kurstaki recipient was studied under environmentally relevant laboratory conditions in vitro, in soil, and in insects. Plasmid transfer was detected in vitro at temperatures of 5 to 37°C, at pH 5.9 to 9.0, and at water activities of 0.965 to 0.995, and the highest transfer ratios (up to 10(−1) transconjugant/donor) were detected within 4 h. In contrast, no plasmid transfer was detected in nonsterile soil, and rapid formation of spores by the introduced strains probably contributed most to the lack of plasmid transfer observed. When a B. thuringiensis subsp. kurstaki strain was used as the donor strain, plasmid transfer was detected in killed susceptible lepidopteran insect (Lacanobia oleracea) larvae but not in the nonsusceptible coleopteran insect Phaedon chocleriae. When a B. thuringiensis subsp. tenerbrionis strain was used as the donor strain, no plasmid transfer was detected in either of these insects even when they were killed. These results show that in larger susceptible lepidopteran insects there is a greater opportunity for growth of B. thuringiensis strains, and this finding, combined with decreased competition due to a low initial background bacterial population, can provide suitable conditions for efficient plasmid transfer in the environment.